KONTEKSTUALISASI KONSEP PEMBELAAN TERPAKSA (NOODWEER EXCES) DALAM TINDAK PIDANA PENGANIAYAAN - Lengkong, Lonna Yohanes; Situmeang, Tomson; Sianipar, Christine Nataniar (Honeste Vivere, 2025)
In the Indonesian Criminal Code (KUHP), there is a concept known as a criminal elimination reason, which allows a person who commits an act that would normally be considered a crime to go unpunished. One such reason is the concept of forgiveness, which eliminates the perpetrator's guilt. This means that even though their actions are proven to violate the law, the perpetrator is not punished due to the elimination of their guilt. An example of such a concept is Forced Defense that exceeds the limit (noodweer excesses). This study focuses on the regulation of excessive forced defense (noodweer exces) according to criminal law in Indonesia, as well as the application of this concept in a specific court decision. The research method used is normative legal research, with a case approach, using various legal materials such as legislation, decisions, expert opinions, legal dictionaries, law journals, and encyclopedias. The study's findings indicate that the defendant has fulfilled all the elements of excessive forced defense (noodweer exces) as regulated in Article 49, Paragraph (2) of the Criminal Code. It was found that the defendant did not intentionally stab the victim with a knife due to being in a state of great shock at the time